2021
DOI: 10.1017/s0033291720004912
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of psychological distress among individuals exposed to the 9/11 World Trade Center disaster

Abstract: Background Individuals present in lower Manhattan during the 9/11 World Trade Center (WTC) disaster suffered from significant physical and psychological trauma. Studies of longitudinal psychological distress among those exposed to trauma have been limited to relatively short durations of follow-up among smaller samples. Methods The current study longitudinally assessed heterogeneity in trajectories of psychological distress among WTC Health Registry enrollees – a prospective cohort healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…This study's qualitative findings are relatively consistent with the results of a 14-year post-9/11 study of members of a registry of affected individuals, 44% of whom were injured, especially with fractures and dislocations, burns, and head injuries. 1 Long-term MH findings of the existing quantitative research on disaster survivors [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] resonate with this long-term study's qualitative findings. The 9/11 study 1 found that emotional distress and employment difficulties arising from the disaster generally improved across time; for some, however, these problems continued for long periods, changing people's lives forever.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…This study's qualitative findings are relatively consistent with the results of a 14-year post-9/11 study of members of a registry of affected individuals, 44% of whom were injured, especially with fractures and dislocations, burns, and head injuries. 1 Long-term MH findings of the existing quantitative research on disaster survivors [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] resonate with this long-term study's qualitative findings. The 9/11 study 1 found that emotional distress and employment difficulties arising from the disaster generally improved across time; for some, however, these problems continued for long periods, changing people's lives forever.…”
Section: Discussionmentioning
confidence: 67%
“…This study's qualitative findings are relatively consistent with the results of a 14-year post-9/11 study of members of a registry of affected individuals, 44% of whom were injured, especially with fractures and dislocations, burns, and head injuries. 1 Long-term MH findings of the existing quantitative research on disaster survivors [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] resonate with this long-term study's qualitative findings. A central strength of the current study is its prospective longitudinal, post-disaster follow-up, allowing survivors to describe their experiences and outcomes over a very long period of time spanning the time of the bombing to almost a quarter of a century later.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…First, in contrast to studies that have examined rescue and recovery workers (e.g., Feder et al., 2016; Maslow et al., 2015; Pietrzak et al., 2014), we analyzed data from community members, which increases the generalizability of the results to community samples. This also is important because trajectories of general distress post‐9/11 have been shown to differ between community members and rescue and recovery workers, with the former more likely to be in higher distress classes (Ko et al., 2021). Second, we analyzed data from the largest sample to date ( N = 37,545 enrollees in the WTCHR).…”
mentioning
confidence: 99%